A framework for involving the young generation in transportation planning using social media and crowd sourcing. (October 2020) - Anik, Md Asif Hasan; Sadeek, Soumik Nafis; Hossain, Moinul; Kabir, Shafquat
Abstract: To ensure that decisions are made reflecting public needs, public participation has become an indispensable part of the modern transportation planning process. However, it has been a challenging task to obtain inputs from the youth for planning purposes through conventional public participation approaches, such as, focus group discussions. This research employs social media and crowdsourcing to engage with the youths of Dhaka city, Bangladesh, to understand their vision of a sustainable transportation system and pathways to achieve it. Then it compares the findings with those obtained from the experts involved in transportation planning. At first, text mining was applied to synthesize useful information from the topics and comments of the posts made by members in a Facebook discussion group consisting of 3000 members which were maintained for almost 1.5 years. Based on the findings of text mining, an online questionnaire survey was conducted, involving both the transportation experts and the youths to ascertain and prioritize various aspects of sustainable modes of transport, e.g., walking, cycling, and public transport through Analytic Hierarchy Process (AHP). Findings suggest similarities as well as variations between the youths and the experts in prioritizing different components of the transport system. For instance, while the experts prioritized adequate walking facilities the most, the young generation emphasized the most on proper public transport environment. Both the groups highly prioritized women-only buses, separate crossing facilities for cyclists, evening lights on sidewalks, however, they exhibited different levels of priority on the introduction of air-conditioned buses, road signs, toilets and dustbins near the sidewalk, etc. Finally, the study proposes ways to create a shared vision of a sustainable transportation system by considering both the conforming and divergent views of the experts and the young generation. Highlights: A framework to assess efficacy of social media in transport planning. Methodology involved text mining and topic modeling of social media and FGD data. AHP compared perception of experts and the youth on sustainable transportation. Social media and FGDs can complement each other in transportation planning. A planning framework was proposed involving social media and crowd sourcing.